Ternate Spice Route Heritage : Optimizing Historical Legacy for Education - Fathnun Tan; Muhammad Assagaf; Ahmad Talib; Aisyah Bafagih; Syahnul Sardi Titaheluw; Umar Tangke; Ali Lating; Ibnu W. Laitupa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
The Spice Route is one of the most important historical heritages that made Ternate a global trading center since the 15th century. The presence of spices, especially cloves and nutmeg, attracted the attention of European nations and brought significant changes in political, social, and cultural aspects in North Maluku. This article discusses the use of the Spice Route heritage site in Ternate City as a medium for history education. Research results show that experiential learning at heritage sites can increase students' interest in learning while strengthening their understanding of Ternate's role in global trade. The article also offers strategic recommendations, including the development of a Spice Route curriculum, the use of digital technology, multi-party collaboration, strengthening local identity, and improving teacher competence. With a contextual and interactive approach, the historical heritage of the Spice Route can become a source of inspiration as well as a means to build character.